Insight into Asymmetry in the Impact of Different Types of ENSO on the NAO - Peng Zhang; Zhiwei Wu (Climate, 2023)
Understanding the influence of the El Niño–Southern Oscillation (ENSO) on the North Atlantic Oscillation (NAO) is of critical significance for seasonal prediction. The present study found that both Niño3.4 sea surface temperature anomaly (SSTA) intensity and east-west gradient in the mid-low latitude Pacific determine the linkage between ENSO and the NAO. Based on Niño3.4 SSTA intensity and the east-west gradient, ENSO events are classified into three types: strong intensity, weak intensity-strong gradient (WSG), and equatorial ENSOs. Note that the former two types are usually concurrent with a strong zonal SSTA gradient. In contrast, equatorial ENSO is often associated with weak intensity-weak gradient SSTAs confined in the equatorial Pacific. The anomalous circulation patterns in response to the three types of ENSO exhibit asymmetric features over the North Atlantic. The WSG-El Niño associated circulation anomaly resembles a negative NAO-like pattern, yet the strong and equatorial El Niño associated circulation anomalies show a neutral-NAO pattern. For La Niña events, their impact on the NAO mainly depends on the cold SSTA position rather than their intensity. The strong and WSG-La Niña associated negative SSTAs are centered in the equatorial-central Pacific and favor a steady positive NAO-like anomaly. The cold SSTA center of equatorial La Niña shifts to the equatorial-eastern Pacific and cannot profoundly influence the North Atlantic climate. The physical mechanisms are also investigated with a general circulation model.